Volcanic hazard and risk assessment at Reykjanes, vulnerability of infrastructure - Þóra Björg Andrésdóttir 1983- (2018)
Volcanic eruptions can have serious consequences, both locally and globally. In Iceland there is a high eruption frequency, where the volcanism is affected by the North Atlantic plate boundary and the hot spot underneath the island. Some areas experience long periods between volcanic activity and because of that, the knowledge of volcanic threat is not in the living memory of the public. Many volcanos have not erupted after recent advances in technology and therefore have not been observed with modern equipment. The Reykjanes peninsula, in SW Iceland, has five volcanic systems with SW-NE orientation, where volcanic activity occurs in episodes, the last ended in the Reykjanes fires 1210-1240. The Reykjanes peninsula is highly populated with many critical infrastructures connecting the urban area that makes hazard assessment very important. In order to implement this assessment, we followed a well-established methodology of evaluating volcanic hazards. This includes a geological database of eruption events throughout the Reykjanes Peninsula, analysis of a spatial probability map and local intensity map and a more detailed analysis of the westernmost part of the Peninsula around the urban areas of Grindavík, Vogar and Keflavík. With these steps the following questions: “Where are the most probable areas of vent opening (hosting a volcanic eruption)”, “What is the most likely event”, and “Where is it most likely that critical infrastructure will be affected”, can be answered. Eldgos geta haft víðtækar afleiðingar, ekki einungis fyrir nærumhverfi heldur einnig á heimsvísu. Ísland er mjög eldvirkt, með háa eldgosatíðni og er eldvirknin tengd stöðu landsins á flekaskilum og heitum reiti undir landinu. Langur tími getur þó liðið á milli goshrina og því má leiða líkur að því að afleiðingar þeirra gosa séu ekki lengur í minni manna. Jafnframt hafa mörg þessara eldgosa einnig átt sér stað fyrir tíma vöktunar og því líklegt að síðustu gos á einhverjum svæðum hafi ekki verið rannsökuð með nútímatækni. Á Reykjanesskaga eru ...